The Role of Industrialization on Employment and Economic Growth in South Africa - Habanabakize, Thomas; Dickason-Koekemoer, Zandri (International Journal of Economics and Financial Issues, 2023)
Nowadays economic performance and people’s well-being are driven by various factors linked to technological improvement and industrialization. South Africa is one of the countries that adopted technology and innovation to improve its economic performance and employment conditions. However, the country is still facing a growing unemployment rate and sluggish economic growth. The current study investigated the role of industrialization in heightening employment and economic growth. The autoregressive distributed lag (ARDL) and error correction model (ECM) approaches were applied to time series data from 1998 to 2019. Empirical findings indicated that industrialisation has a significant impact on South African economic growth and employment opportunities. While automotive, food and beverage, chemical and metal industries positively affect economic growth; employment growth is fuelled by high production in food and beverage, chemical, automotive and metal industries. Nonetheless, high production in clothing and chemical industries have adverse effects on economic and employment growth respectively. In the short run, employment behaviour is determined by the production of metal, food and beverages industries while changes in economic growth are driven by production in the automotive and metal industries. Grounded on findings, South African policymakers should consider pro-industrialization strategies, especially in those industries whose production is highly demanded such as metal, food and beverages. These industries enhance trade and the latter improve economic growth and create employment.